In A Predicament All My Life : a Collection of Poems. - Asobo, Binwi (Langaa RPCIG, 2015)
In A Predicament All My Life marks out some of the distressing ills of the postcolonial elite and the challenges of present-day African societies and cultures. The Poems in this collection bring into conversation precolonial Africa and Africa since colonialism. In particular, the poems explore Cameroon's predicament, its reunification traits, and its existential challenges. They represent a people who are out of favour, have lived in misery for most of their lives but are determined to stand firm and seek justice. In addition, the poems depict how women deal with gender oppression in a patriarchal society caught between and betwixt.